Implementasi Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) Untuk Menentukan Kualitas Buah Mangga Terbaik - Santri W Pasaribu; Ester Rajagukguk; Maret Sitanggang; Robbi Rahim; Leon Andretti Abdillah (JURIKOM (Jurnal Riset Komputer), 2018)
Mango fruit is the most popular fruits by the people of Indonesia. With several different types of varieties, it becomes an attractive choice for the public to eat. But in fact, it is difficult to determine what kind of mango is superior, certainly judging from the quality of the fruit produced. The number of criteria that affect the quality of good fruit, would be a problem to be solved by using decision support system. Application of good methods in decision support systems greatly affects effective outcomes in determining the quality of mangoes. Many methods are currently developing, including ELECTRE, MOORA, VIKOR, and PROMETHEE. The method has advantages and disadvantages in the processing in accordance with the weight of the criteria specified. In this research the researcher use the method of MOORA (Multi-Objective Optimization on the Basis of Ratio Analysis), Multi-Objective Optimization Method on the Basis of Ratio Analysis (MOORA) is chosen because it can determine the weight value for each attribute, then proceed with the ranking process which will select the best alternative from a number of alternatives.